Enteric fever masquerading as parotitis - Dutta, Sanjeev; Khullar, Niharika (International Journal of Contemporary Pediatrics, 2024)
Parotitis is commonly associated with viral infections, while some cases can be bacterial. Parotitis with enteric fever is very rare and has not been reported in pediatric population. An 8-years-old girl presented with parotitis, high grade fever, abdominal pain and vomiting. Salient examination findings were bilateral parotitis, cervical lymphadenopathy on right side, tonsillar hypertrophy with exudates over the right tonsil. Abdominal examination did not reveal any hepatosplenomegaly. Blood culture showed Salmonella paratyphi A., while other test for etiology of parotitis were non-conclusive. Parenteral ceftriaxone was given for a total duration of 14 days. The child responded well clinically and was kept under close follow-up. Presence of parotitis with enteric fever is a very rare finding. Blood culture is a gold standard test for diagnosing enteric fever. It should be incorporated in first line investigations in cases presenting with high grade fever and parotitis.